Design of information hiding algorithm for multi-link network transmission channel - Fu, Songyin; Wang, Rangding (Penerbit Universiti Kebangsaan Malaysia, 2019)
Traditional channel information hiding algorithms based on m-sequence for multi-link network transmission, which apply m-sequence to channel coding information hiding system, do not analyze the upper limit of hiding capacity of multi-link network transmission channel system, and do not consider the hidden danger of overlapping secret information when embedding secret information is too large. It has the defects of low efficiency, poor accuracy and large storage cost. This paper designs an information hiding algorithm for multi-link network transmission channel based on secondary positioning, it uses RS code M public key cryptosystem to pre-process secret information and improve the security of information; calculates the upper limit of hiding capacity of multi-link network transmission channel system through information hiding capacity analysis model, and determines whether the hiding capacity exceeds the secret information. Secondary location and cyclic shift mechanism are introduced to improve the randomness of location selection and avoid overlapping of secret information. The experimental results show that the proposed algorithm has a great advantage in memory cost. When the channel SNR is 0 dB and 8 dB, the normalization coefficients are 0.87 and 1.04, respectively. This shows that the algorithm has a high accuracy in extracting secret information. The average time spent on hiding information is 2.04 s, indicating that the algorithm has high information hiding rate and storage efficiency.